Thinning intensity influences the C:N:P stoichiometry in forest ecosystems: A global synthesis - Chongwei Fan; Guiyao Zhou; Hongyang Chen; Zhenggang Du; Ruiqiang Liu; Yanghui He; Changjiang Huang; Shuying Qiu; Yimin Zhu; Jie Li; Xuhui Zhou (Geoderma, 2025)
Forest thinning potentially alters carbon (C), nitrogen (N), and phosphorus (P) cycles, thereby affecting their C:N:P stoichiometry as well as the key ecosystem services they support. Despite the fact that numerous individual studies and a few meta-analyses have been conducted to examine thinning effects on ecosystem C and N cycles, how forest thinning, especially its intensity, affects the C:N:P stoichiometry of plants, soil, and microbes remains poorly known. Here, we carried out a global meta-analysis of 779 paired observations from 136 peer-reviewed articles to assess effects of forest thinning on C:N:P stoichiometry of plants, soil, and microbes in global forests. Our results showed that, on average, forest thinning significantly increased soil C and P pools by 5.0% and 11.1%, and microbial biomass C, N, and, P pools by 9.3%, 12.0%, and 38.4%, respectively. In contrast, forest thinning decreased plant P pool, soil C:P and N:P ratios, and microbial C:N and N:P ratios. More importantly, the effects of forest thinning on C:N:P stoichiometry largely varied with forest thinning intensity. Specifically, heavy thinning significantly decreased plant C:N ratios and soil N:P ratios, whereas light and moderate thinning had positive or insignificant effects on C:N:P stoichiometry. Thinning-induced changes in the C:N, C:P, and N:P ratios were positively correlated with mean annual temperature (MAT) and mean annual precipitation (MAP), but negatively with post-thinning duration and stand age. These findings highlight the impact of thinning intensity on the connection between above- and belowground processes, which may decouple the biogeochemical cycles of C, N, and P in forest ecosystems. Future forest management could implement an appropriate forest thinning intensity to ensure ecosystem functionality and maintain the balance and stability of ecosystem elements.